Fabrication of 4H-SiC n-channel IGBTs with ultra high blocking voltage. (March 2018) - Yang, Xiaolei; Tao, Yonghong; Yang, Tongtong; Huang, Runhua; Song, Bai
Abstract: Owing to the conductivity modulation of silicon carbide (SiC) bipolar devices, n-channel insulated gate bipolar transistors (n-IGBTs) have a significant advantage over metal oxide semiconductor field effect transistors (MOSFETs) in ultra high voltage (UHV) applications. In this paper, backside grinding and laser annealing process were carried out to fabricate 4H-SiC n-IGBTs. The thickness of a drift layer was 120 μ m, which was designed for a blocking voltage of 13 kV. The n-IGBTs carried a collector current density of 24 A/cm 2 at a power dissipation of 300 W/cm 2 when the gate voltage was 20 V, with a differential specific on-resistance of 140 mΩ·cm 2 .